1997
DOI: 10.1515/zna-1997-0401
|View full text |Cite
|
Sign up to set email alerts
|

ab initio Calculation of 33S Quadrupole Coupling Constants. Reanalysis of the 33S Hyperfine Structure in the Rotational Spectrum of Thiirane

Abstract: We present quantum chemical calculations on the MP4(SDQ) level with basis sets of high local quality to determine the nuclear quadrupole coupling tensor of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…To solve this problem in the vibrational structure, Allen et al (9) reinvestigated the infrared and Raman spectra of ethylene sulfide, including its deuterated derivatives (ethylene sulfide-d 2 and -d 4 ), and assigned all observed bands with the help of their theoretical calculations. More recently, Kirchner et al (10) observed the Fourier transform microwave spectrum of ethylene sulfide for 32 S and 33 S isotopic species. Molecules with three membered rings, like ethylene sulfide, have been the subject of various calculations (10,11) in order to study ring strain.…”
Section: Note the R 0 Structure Of Ethylene Sulfidementioning
confidence: 99%
See 1 more Smart Citation
“…To solve this problem in the vibrational structure, Allen et al (9) reinvestigated the infrared and Raman spectra of ethylene sulfide, including its deuterated derivatives (ethylene sulfide-d 2 and -d 4 ), and assigned all observed bands with the help of their theoretical calculations. More recently, Kirchner et al (10) observed the Fourier transform microwave spectrum of ethylene sulfide for 32 S and 33 S isotopic species. Molecules with three membered rings, like ethylene sulfide, have been the subject of various calculations (10,11) in order to study ring strain.…”
Section: Note the R 0 Structure Of Ethylene Sulfidementioning
confidence: 99%
“…More recently, Kirchner et al (10) observed the Fourier transform microwave spectrum of ethylene sulfide for 32 S and 33 S isotopic species. Molecules with three membered rings, like ethylene sulfide, have been the subject of various calculations (10,11) in order to study ring strain.…”
Section: Note the R 0 Structure Of Ethylene Sulfidementioning
confidence: 99%
“…A (20s15p4d2f )/[12s9p4d2f] basis for sulfur was constructed in previous work (16) and applied here to SO 3 in ab initio calculations including electron correlation. The SO 3 was held at the planar structure determined by microwave spectroscopy (8) with an OSO angle of 120°and the SOO bond length held fixed at the estimated equilibrium value of 1.4175 Å.…”
Section: So 3 Monomermentioning
confidence: 99%
“…For small molecules, the measurement of 4-methyl-1,2,4-triazole CI (QCISD) [ 19] values, while various Restricted Active Space SCF (RASSCF) [20] results yield a smaller correlation correction (see also [10] for results for formamide). Ab initio calculations of NQCC's have also been performed recently on molecular clusters [21,22] at the SCF level of theory, and on solids, by Schwartz and co-workers employing DFT [23], and by Palmer within the SCF approximation [24 -26], Cremer and Kruger [27] compared calculated EFG and measured NQCC's for a series of molecules -both small and large -containing 14 N. Using the more accurate results for small molecules, they determined an "effective quadrupole moment" for 14 N, which they applied to correct the results for larger systems. Similar scaling has been sometimes used for 14 N by other authors, see e. g. [6].…”
Section: Introductionmentioning
confidence: 99%
“…We have also performed test calculations using four different MC-SCF wavefunctions for 1-methyl-1,2,3-triazole, and the variations of the results are similar to those displayed in Table II. For the other azoles we discuss only the NMR signal linewidths, since there are no experimental data for their NQCC's. The calculated linewidths for all the 14 N signals in the azoles studied here are shown in Table III. The available experimental data we quote are from the end of the seventies [29,30].…”
mentioning
confidence: 99%